Autophagy regulation as a promising approach for improving cancer immunotherapy. (10th April 2020) - Ishimwe, Nestor; Zhang, Wenbin; Qian, Jieying; Zhang, Yunjiao; Wen, Longping
Abstract: Autophagy plays a critical role in intracellular metabolism and maintaining cellular homeostasis. Certain tumor cells present a higher basal autophagy rate and autophagy inhibition can lead to impaired metabolic dysfunction in autophagy-dependent tumor cells. Autophagy status in immune cells dictates their fate and response to antigen; however, autophagy in immune cells may be beneficial or detrimental depending on the developmental stage of the cell and more specifically its degree of differentiation. Autophagy-deficient hosts present variations in many metabolites, proteins and enzymes that may have tumor-promoting or -inhibiting effects. The centrality of autophagy in the metabolism of some cancers and immune cells poses as a critical target whose mechanisms must be further unraveled to optimize patient response and prevent tumor recurrence. Highlights: Immune cells signaling pathways are activated by extracellular and intracellular signals. Autophagy regulators may dictate immune cells response. Combinatorial treatment strategy of autophagy modulators and other cancer drugs pertain a potential future cancer therapy. Autophagy modulators contribute to immune cells activation.